Nitro-Oleic Acid Prevents Hypoxia- and Asymmetric Dimethylarginine-Induced Pulmonary Endothelial Dysfunction - Koudelka, Adolf; Ambrozova, Gabriela; Klinke, Anna; Fidlerova, Tana; Martiskova, Hana; Kuchta, Radek; Rudolph, Tanja K; Kadlec, Jaroslav; Kuchtova, Zdenka; Woodcock, Steven R; Freeman, Bruce A; Kubala, Lukas; et al. (Cardiovascular drugs and therapy, 2016)
RATIONALE: Pulmonary hypertension (PH) represents a serious health complication accompanied with hypoxic conditions, elevated levels of asymmetric dimethylarginine (ADMA), and overall dysfunction of pulmonary vascular endothelium. Since the prevention strategies for treatment of PH remain largely unknown, our study aimed to explore the effect of nitro-oleic acid (OA-NO2), an exemplary nitro-fatty acid (NO2-FA), in human pulmonary artery endothelial cells (HPAEC) under the influence of hypoxia or ADMA. METHODS: HPAEC were treated with OA-NO2 in the absence or presence of hypoxia and ADMA. The production of nitric oxide (NO) and interleukin-6 (IL-6) was monitored using the Griess method and ELISA, respectively. The expression or activation of different proteins (signal transducer and activator of transcription 3, STAT3; hypoxia inducible factor 1α, HIF-1α; endothelial nitric oxide synthase, eNOS; intercellular adhesion molecule-1, ICAM-1) was assessed by the Western blot technique. RESULTS: We discovered that OA-NO2 prevents development of endothelial dysfunction induced by either hypoxia or ADMA. OA-NO2 preserves normal cellular functions in HPAEC by increasing NO production and eNOS expression. Additionally, OA-NO2 inhibits IL-6 production as well as ICAM-1 expression, elevated by hypoxia and ADMA. Importantly, the effect of OA-NO2 is accompanied by prevention of STAT3 activation and HIF-1α stabilization. CONCLUSION: In summary, OA-NO2 eliminates the manifestation of hypoxia- and ADMA-mediated endothelial dysfunction in HPAEC via the STAT3/HIF-1α cascade. Importantly, our study is bringing a new perspective on molecular mechanisms of NO2-FAs action in pulmonary endothelial dysfunction, which represents a causal link in progression of PH. Graphical Abstract ᅟ.
Keywords: Cell Survival; Humans; hypoxie buňky; Oleic Acids; kyseliny olejové; STAT3 Transcription Factor; Interleukin-6; oxid dusnatý; Asymmetric dimethylarginine; Cell Adhesion; Hypoxia; lidé; Nitric Oxide; Cells, Cultured; Hypoxia-Inducible Factor 1, alpha Subunit; Nitro-oleic acid; Arginine; faktor 1 indukovatelný hypoxií - podjednotka alfa; transkripční faktor STAT3; pohyb buněk; mezibuněčná adhezivní molekula-1; Endothelial Cells; interleukin-6; kultivované buňky; Human pulmonary artery endothelial cell; Cell Movement; arginin; Pulmonary hypertension; endoteliální buňky; synthasa oxidu dusnatého, typ III; Intercellular Adhesion Molecule-1; buněčná adheze; arteria pulmonalis; Nitric Oxide Synthase Type III; Cell Hypoxia; viabilita buněk; Pulmonary Artery